THE HOLY PLACE OF OUR PEOPLE – KHOJAIGOR TEMPLE (American Journal of Pedagogical and Educational Research, 2023)
The article talks about the shrine in the Northern Surkhan oasis, in particular, in the village of Taytavo in the Sariosi region.